Efektivitas Pratikum Industri Perjalanan Dalam Menguatkan Karakter Disiplin Mahasiswa Jurusan Pariwisata Budaya: (Studi Kasus UHN I Gusti Bagus Sugriwa Denpasar) - Ariputra, I Putu Suyasa; Nurdin, Encep Syarief; Ruyadi, Yadi; Prima Dewi PF, Kadek Aria; Dahliyana, Asep; Hakam, Kama Abdul; Ganeswara, Ganjar Muhammad (Cetta: Jurnal Ilmu Pendidikan, 2025)
Education serves not only as a medium for transferring knowledge but also as a process of shaping values and character that are manifested in real behavior. One of the fundamental character traits that must be nurtured in higher education is discipline, particularly in the context of globalization and the competitive tourism industry that demands professionalism. This study aims to analyze the achievement of students’ discipline character in the Cultural Tourism Department through the Travel Industry Practicum, based on five key indicators: obedience, compliance, loyalty, regularity, and orderliness. The research employed a quantitative descriptive approach using a questionnaire instrument adapted from Patmawati (2013). The population consisted of 75 students from the 2021 cohort, with a sample of 43 respondents determined through Slovin’s formula and convenience sampling. The findings reveal that during the initial phase of the practicum, several weaknesses were observed in students’ discipline, such as tardiness, uniform neatness, and consistency in task completion. However, after completing the practicum over one semester, all discipline indicators showed significant improvement, reaching the “very good” category with an average score of 4,66. These results indicate that practical field experience combined with institutional guidance effectively strengthens students’ internalization of discipline values. In conclusion, the Travel Industry Practicum is not only a vehicle for applying academic theory, but also serves as an effective strategy for character building. The results of this study make an important contribution to strengthening Thomas Lickona's noble character education framework through its application in higher education, particularly in the field of tourism. These findings can serve as a strategic basis for policy formulation and curriculum development oriented towards the formation of disciplinary character, so that higher education can produce graduates who are not only academically competent but also excel in work ethic and character values.